Management of Thermal Burns over Breast – Our Experience - Somala Prathyusha; Ravi Kumar Chittoria; Barath Kumar Singh P. (International Journal of Biomedical Innovations and Engineering, 2023)
The intricate challenge of restoring normal anatomy with minimal deformity in burns over the breast region has prompted the development of innovative tissue regeneration approaches. Addressing the complex nature of challenging wound patterns necessitates a multidisciplinary team with diverse expertise. In our concerted effort, we have successfully integrated advanced reconstructive techniques with regenerative medicine modalities to enhance outcomes in the intricate realm of complex breast reconstruction post-thermal burns. Our approach involves a comprehensive strategy that considers the unique characteristics of the breast tissue. We prioritize a combination of cutting-edge reconstructive methods and regenerative medicine interventions to achieve optimal results. By leveraging the collective knowledge of experts in plastic surgery, dermatology, and regenerative medicine, we have refined a protocol that emphasizes both functional and aesthetic aspects of breast restoration. The synergy between innovative reconstructive techniques, such as autologous tissue transfer and flap procedures, and regenerative medicine interventions, including stem cell therapy and tissue engineering, forms the cornerstone of our approach. This article provides a detailed overview of our integrated methodology, shedding light on the intricacies of treating thermal burns on the breast. Through this collaborative and forward-thinking approach, we aim to contribute to the evolving landscape of burn care, pushing the boundaries of what is achievable in restoring normalcy after such traumatic injuries.
Keywords: Breast; management; regenerative therapy; thermal burns